Improvement of Native Pastures With Stylosanthes Humilis H.B.& K. in Semi-Arid Regions - Singh, C B; Gupta, S R; Gupta, J N (Annals of Arid Zone, 2016)
Under various cultivation and grazing treatments, Townsville stylo (Stylosantiles humilis H.B.& K.) Sellima-Dichanthium contributed substantially to the productivity of native grasses pasture at all the sites. Grazing helped beller utilization of the grass herbage at the early stages of growth and promoted vigorous stylo growth by eliminating competition from the native grasses. Cultivation increased the overall site productivity, especially the stylo and its proportion in the herbage at the grazed sites. Unlike stylo, the production of native grasses was more stable on the ungrazed sites. The association between grass biomass and stylo was significantly negative due to vigorous growth of grass on ungrazed uncultivated sites. Such association was nonsignificant on the cultivated or grazed sites.